Exteroception and the perceived (dis)connection of the body and the self: implications for the understanding of dissociative self-experiences in borderline personality disorder - Löffler, Annette; Kleinböhl, Dieter; Gescher, Dorothee Maria; Panizza, Angelika; Bekrater-Bodmann, Robin (Personality disorders, 2025)
Dissociation describes a state of altered consciousness in which self-related functions are no longer integrated. In its extreme form, the self is perceived as detached from the physical body, resulting in so-called out-of-body experiences (OBEs). It has been previously proposed that altered bottom-up sensory integration contributes to this kind of dissociative self-experience, which is supported by results on the experimental induction of OBEs in nonclinical individuals by appropriate visuotactile stimulation. Borderline personality disorder (BPD) is characterized by disturbed body representation which covaries with clinical dissociation levels; however, whether dissociative self-experiences in BPD also rely on bottom-up sensory processes is unknown. In the present study, we experimentally induced OBEs in a sample of 22 participants with the diagnosis of current BPD (cBPD) as well as 16 individuals with remitted BPD and 20 nonclinical controls. Results revealed higher proneness for OBEs in cBPD compared to both other groups. Processing of affective sensory information, in terms of pain and emotional acoustic stimuli, was not influenced by experimentally provoked dissociative self-experiences. Changes in clinical dissociation were significantly related to the extent of experimentally induced body-self detachment in the cBPD group. Our results suggest that altered processing of exteroceptive sensory information contributes to clinically relevant dissociative self-experiences in BPD, which appears to normalize when the disorder is in its remitted stage. We discuss our results in the context of altered weighting of exteroceptive and interoceptive information in a predictive coding framework. (PsycInfo Database Record (c) 2025 APA, all rights reserved)